The Spillover Effect of Consolidating Securitization Entities on Small Business Lending - Dou, Yiwei (The Accounting Review, 2021)
ABSTRACT I investigate how the consolidation of securitization entities under SFAS 166 and 167 spills over to banks' supply of small business loans, which are rarely securitized in the United States. This spillover operates through two channels. (1) In the leverage channel, consolidating banks downsize their entire loan portfolios, both small business loans and other loans, in response to increased leverage after consolidation. (2) In the risk management channel, consolidating banks adjust the mix of loans to maintain optimal diversification. The adjustment can increase the supply of small business loans when their performance covaries positively with the performance of other loans. I find that, on average, banks that consolidate more securitized assets reduce small business lending; consequently, counties with a greater market share of consolidating banks experience slower growth in small businesses. I also identify a small group of banks with sufficiently large positive performance covariance that increase small business lending. Data Availability: All untabulated results are available upon request. JEL Classifications: M4; G21.